A new feminist perspective on single motherhood with school-age children - Dogan, Muhammet Fatih (WILEY, 2026)
Objective This research examines the multidimensional nature of the single motherhood experience through a new feminist lens, focusing on how maternal agency is exercised across different sociopolitical contexts. Background While international literature often frames single motherhood within narratives of economic vulnerability and psychosocial deprivation, this study addresses the complexity of these experiences beyond simple victimhood. Methods Employing a qualitative phenomenological design, the study utilized thematic analysis of semistructured interviews with 25 single mothers across T & uuml;rkiye, Greece, and Armenia. Participants were recruited via snowball sampling to capture diverse lived experiences. Results Findings reveal that single motherhood is a complex terrain of vulnerability and resistance. While time poverty and economic precarity create constrained choice, women practice agency through strategic memorialization, matrilineal support networks, and the strategic transformation of maternal roles. Conclusion The study concludes that an intersectional feminist approach is imperative to understand these diverse, non-homogeneous experiences of agency and structural constraint. Implications Policies must be holistic and dignified, moving beyond cash assistance to include accessible childcare, legal counselling for alimony, and psychological support systems that bolster maternal autonomy.
Keywords: agency and resistance; economic vulnerability; intersectionality; new feminism; single motherhood; Family Studies; Social Work